Knowledge and practice regarding junk food among secondary level students - Panthi, Mina (2014)
ABSTRACT: This descriptive study entitled "Knowledge and Practices Regarding Junk Food among Secondary Level Students" was carried out with the objective of to identify the knowledge and practices regarding junk food among secondary level students. This study was conducted in Kalika Higher Secondary School Kalikanagar-12,Nabin Higher Secondary School Devinagar-13, New Horizon Boarding School and SmitriBoarding School, Butwal in Rupandehi, Nepal. The population of the study was students who studied in grade 8, 9, and 10. The total 378 students were selected by using systemic random sampling technique. A pre-tested semi structured questionnaire was used to measure the research variables. The data obtained was analyzed by using descriptive statistics such as frequency, percentage, mean and standard deviation. The study findings revealed that majority of respondents(68%) were between 13-15 years of age, 51.3% were male and 80.4% live in nuclear family.All most all respondents (98.1%) knew about balance diet among them only 53.7% had good knowledge about it, 86.5% respondents knew about the junk food items, 51.9%reported junk food is a packed food 85.4% said junk food is not an alternative food for healthy food. The main source of getting information about junk food was parents itself (30.7%) followed byadvertisement21.2%. Most of the students (88.9%) were known about the effects of junk food, among them 31.3% saidobesity, 27% diabetes mellitus & 12.7% heart disease.Nearly two third respondents (62.4%) faced various problems after consumption of junk food,majority of them, 33% faced stomach pain, 7.7% diarrhea, 4.2% jaundice. Majority of respondents (23%) reported that they didn't improve their diet due to giving less emphasis to the balance diet followed by 22.2% due to lack of time. Practice of respondent regarding junk food revealed that all the respondents were consumed junk food in their daily life. Most of them (53.4%) preferred noodle, 45% respondents spent below Rs.20 daily on junk food purchase,71.2% commonly preferred junk food in noonand maximum respondents (61.4%) skipped lunch followed by breakfast(22.8%) by eating junk food.More than three fourth respondents agreed that their junk food habit increased after left their home (77%) and this habit going to increase day by day (63.2%).Maximum respondents (45.2%)consumed junk food morewhen they are in group (45.2%) followed by travelling (20.6%). In conclusion,most of the school children have some knowledge about the junk food and its possible harmful effects but despite this knowledge,all the school children consumed junk food. Hence, it is necessary to include in the course of school children in depth and need to formulate the policy regarding the food consumption.